ncry.net
ǰλãҳ >> 2(3xʮ4)һ5(xʮ1)=3 >>

2(3xʮ4)һ5(xʮ1)=3

Ϊ2(3x+4)-5(x+1)=6x+8-5x-5=x+3=3,x=0.

2(3xʮ5)+4(xʮ1)=6x+10+4x+4=(6x+4x)+(4+10)=10x+14

1) : 5x-4x=15+3 x=18 2) 6x-2=4x+4 6x-4x=4+2 2x=6 x=3 ӣůů Ϊ,ףѧϰ! ϿҵĻش, 뼰ʱ,(ҵĴġ𰸡ͼ) IJ, ǰĶ! IJҲ㳢۶֬ɰȱȥƸֵ. в, ׷,ֱŪ! 绹µ, ,(Ҫ׷)ⲻ,½⡭

x/(2x+2)+1/(1-x)=3Ⱥͬ(2x+2)(1-x):x(1-x)+(2x+2)=3(2x+2)(1-x)x-x+2x+2=6-6x5x+3x-4=0ʽ:x1,2=(-389)/10

ȴ2x+6-5+5x=3x-3 ,δֱ֪ƵȺ2x+5x-3x=-6+5-3 ٺϲͬ4x=-4 x=-1

:2(3Xʮ4)=3(Xһ3֮l)6x+8=3x-16x-3x=-1-83x=-9x=-3

2x(3x-4x+1)-3x(2x-3) =6x^3-8x^2+2x-6x^3+9x^2 =x^2+2x x=-3 x^2+2x =(-3)^2+2*(-3) =9-6 =3

:(1)(2xһ1)2=x(6xһ3) (2x-1)2=3x(2x-1)(2x-1)2-3x(2x-1)=0(2x-1-3x)(2x-1)=0(x+1)(2x-1)=0 x1=-1 x2=1/2 (2)(2xһ1)2=x2ʮ4xʮ4 (2x-1)2=(x+2)2(2x-1)2-(x+2)2=0(2x-1+x+2)(2x-1-x-2)=0(3x+1)(x-3)=0 x1=-1/3 x2=3 ʲô׿׷, ɱ,ⷢҵͷ,ⲻ,½,лл.o(_)o,ǵúͲ, ףѧϰ!

2[3xһ4(x-1)]ʮ2=3(x-2)2[3x-4x+4]+2=3(x-2)2[-x+4]+2=3(x-2)-2x+8 +2 =3x-6-2x+10 =3x-65x=16x=16/5

17һ2(3xʮ4)=3һ2(xһ1)17-6x-8=3-2x+2-6x+2x=3+2-17+8-4x=5-17+8-4x=-12+8-4x=-44x=4x=4/4=1

վҳ | վͼ
All rights reserved Powered by www.ncry.net
copyright ©right 2010-2021
磬ַϵͷzhit325@qq.com